1) : Réduire chaque expression :

A = 5x * 3

B = - 5x * x

C = - 7 * 3

D = 7 * x

E = A + B + C + D


2) : Réduire les expressions :

A = 7 - (4x - 5) + 3 + (4 -2x)

B = (6x - 7) - 4 - (7 -2x)

C = 3x - (9 - x) + 5 + (4x - 7)

3) : Réduire les expressions :

A = 7x² - (4x² - 5) + 3 + (3x² - 2x + 5)

B = (3x² + 5x - 3 ) - 2 - (x² - 5x - 8)

C = 5 - (7 - 6x) - 3x² - (x² - x + 1)

J'espère que vous m'aiderez, merci.

2

Réponses

2013-03-03T14:01:08+01:00

1) A=15x  B=-5x²   C= -21   D=7x   E= -5x²+22x-21

 

2) A=-6x+19  B=8x-18  C=8x-11

2013-03-03T14:07:00+01:00
1) A=15x
B=-5x^2
C=-21
D=7x
E=-5x^2+22x-21

2) A=7-4x+5+3+4-2x=-6x+19
B=6x-7-4-7+2x=8x-18
C=3x-9+x+5+4x-7=8x-11

3) A=7x^2-4x^2+5+3+3x^2-2x+5=6x^2-2x+13
B=3x^2+5x-3-2-x^2+5x+8=2x^2+10x+3
C=5-7+6x-3x^2-x^2+x-1=-4x^2+7x-3